2021
DOI: 10.1002/adom.202101062
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Thermochromism in All‐Inorganic Lead‐Free Cs3Sb2I9 Perovskite Single Crystals

Abstract: Here, lattice expansion modulated reversible thermochromism (TCM) in all‐inorganic lead‐free Cs3Sb2I9 perovskite single crystals (SCs) is demonstrated. Upon temperature change, Cs3Sb2I9 SC exhibits a reversible color change between red and dark‐brown. The corresponding optical band‐edge modulation and structural phase transition are monitored by temperature dependent UV–vis absorption spectroscopy and X‐ray diffraction study. This observed reversible TCM is attributed to the lattice expansion and strain relaxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…It is noted that size of the obtained single crystals can be increased even further by using a bigger scintillation vial, significantly larger than most of the other Pb‐free perovskites. [ 25 , 26 , 27 , 28 ] The large‐scale uniform rod morphology lays the foundation for the design of centimeter‐level single‐crystal devices. [ 28 , 29 ] It is important to note that the successful application of this method for crystallization depends on the use of H 3 PO 2 , which was added to prevent the oxidation of Cu + , [ 17 ] otherwise nonluminescent Cu 2+ ‐contained compounds can be produced (Figure S1 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that size of the obtained single crystals can be increased even further by using a bigger scintillation vial, significantly larger than most of the other Pb‐free perovskites. [ 25 , 26 , 27 , 28 ] The large‐scale uniform rod morphology lays the foundation for the design of centimeter‐level single‐crystal devices. [ 28 , 29 ] It is important to note that the successful application of this method for crystallization depends on the use of H 3 PO 2 , which was added to prevent the oxidation of Cu + , [ 17 ] otherwise nonluminescent Cu 2+ ‐contained compounds can be produced (Figure S1 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, replacing lead with low toxic or nontoxic ions, such as Sn, Ge, Cu, Bi, and Sb, will result in environmentally friendly perovskites with outstanding photoelectric properties, which has been revealed by pioneering studies (Figure ). For example, Seo et al demonstrated 2D perovskites (DA) 2 MnCl 4 (DA = decylammonium) and (NA) 2 CuBr 4 (NA = nonylammonium) with narrow hysteresis and pressure-sensitive order–disorder phase transitions (Figure ).…”
Section: Perovskitementioning
confidence: 99%
“…Copyright 2022 American Chemical Society. Reproduced with permission from ref . Copyright 2021 Wiley.…”
Section: Perovskitementioning
confidence: 99%
“…The high temperature phase would be converted back to the low temperature phase in moist environments. Recently, lead-free perovskites are developed, [33,34] of which the TC properties are induced by the length change of chemical bonds under different temperatures. For instance, the cesium silver bismuth bromide (Cs 2 AgBiBr 6 ) shows a slight color transition from 25 °C (light red) to 100 °C (dark red) due to the changes in the bond lengths of AgBr and BiBr.…”
Section: Thermo-responsive Materialsmentioning
confidence: 99%